2015
DOI: 10.12816/0024678
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive Symptoms among Hemodialysis and Peritoneal Dialysis Patients

Abstract: Introduction: End stage renal disease (ESRD) affects patient's physical and psychological health. Depression is the most common psychiatric illness among patients with ESRD. This study aimed to identify the prevalence of depressive symptoms among patients undergoing peritoneal (PD) and hemodialysis (HD), also to correlate these symptoms with the demographic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 18 publications
5
38
2
Order By: Relevance
“…Similarly, other studies have shown significant association between depression and level of income. 28 Eighteen percent of the participants in the present study reported poor quality of life. The changes in patients' social relationship and psychological wellbeing due to illness symptoms have been recognized as factors contributing to the poor quality of life.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, other studies have shown significant association between depression and level of income. 28 Eighteen percent of the participants in the present study reported poor quality of life. The changes in patients' social relationship and psychological wellbeing due to illness symptoms have been recognized as factors contributing to the poor quality of life.…”
Section: Discussionmentioning
confidence: 60%
“…Although establishing the diagnosis of depression by a psychiatrist is more reliable than questionnaire assessment, our patients favored the survey approach. One obvious strength of the study protocol was to minimize the effects of overlapping symptoms of uremia as much as possible and to correlate the adequacy of HD with depression; both were overlooked in several previous studies that resulted in an overestimation of the prevalence of depression in dialysis patients (14,15). We are planning a new survey that involves more patients from several dialysis centers with evaluation of pre and post-HD PHQ-9 scores to clarify the role of uremic symptoms on the diagnosis of depression, with longer follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the similarity of many depression symptoms such as lack of interest, poor appetite, insomnia, and weakness with symptoms of uremia, we instructed the patients to complete the PHQ-9 form the same day few hours' post-HD sessions, when uremic symptoms are the least. This critical precaution was overlooked in similar studies conducted formerly in the Middle and the Far East, that resulted in a considerable overestimation of the rate of depression in such patients (14,15). We categorized the patients, according to the results of the PHQ-9 scores, considering a score of 10 or more as an indicator of significant clinical depression that required intervention, on the other hand, scores more than 20 suggested severe depression that required psychiatric consultation or referral.…”
Section: Methodsmentioning
confidence: 99%
“…A total is then calculated by adding the points of each question and the value obtained is between 20 and 80. The interpretation of the obtained score is as follows: <50: absence of depression; 50–59: mild depression; 60–69: moderate depression; ≥70: severe depression [12,13]. …”
Section: Methodsmentioning
confidence: 99%